Analisis Keberpihakan Presiden dalam Kampanye Politik Berdasarkan Pasal 281 Undang-Undang No 7 Tahun 2017 tentang Pemilu - Indra Purwanto; Ali Maskur (Jurnal USM Law Review)
This research aims to analyze the President's partisanship in political campaigns based on Article 281 of Law Number 7/2017 on General Elections. This issue is important because it concerns the integrity of democracy and public trust in the institution of the presidency. The urgency of this study increased after the President of the Republic of Indonesia showed a symbolic gesture of support for one of the candidate pairs and conveyed his intention to “cawe-cawe” in organizing the 2024 Election. This research uses an empirical juridical method with a literature study approach to legislation, legal literature, and content analysis of print and electronic media coverage. The novelty of this research lies in the focus of analysis on the ambiguity of Article 281 norms that have not specifically regulated the role of the president as a political actor as well as head of state in the context of the campaign. The results show that the President's actions have the potential to violate the principle of neutrality as stipulated in Article 281. On the other hand, the norm is considered multi-interpretive and potentially contradicts Article 4 of the 1945 Constitution, which places the President as the holder of government power. This study concludes that Article 281 of Law No. 7/2017 needs to be revised because it has the potential for multiple interpretations of the President's position in the constitutional system, and risks blurring the line between political authority and ethics of state office.